PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN TELEKOMUNIKASI - Firdayanti, Fiskha Kostaria (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is observing the financial performance to the stock return for Telecommunication Companies which are listed in Indonesia Stock Exchange (IDX) in the year of 2009 â 2012. The purpose of this research is to know the financial performance to the stock return. The samples collection method is using purposive sampling method out of nine companies which are listed in Indonesia Stock Exchange (IDX) between 2009 â 2012, only seven companies are used as the research samples. The dependent variable in this research is stock return, while the independent variables are CR, QR, NPM, ROA, ROE, and EVA. The data analysis method is using multiple regressions analysis. The research result shows that CR, QR, NPM, ROA, ROE, EVA are simultaneously have no influence to the stock return. Partially shows that CR, QR, NPM, ROA, ROE, dan EVA do not have significant influences to the stock return.Keywords: CR, QR, NPM, ROA, ROE, EVA, and Stock Return